Principles of tourism 1 - Manzano, Ronald G.; Santos, Buen (Quezon City MaxCor Publishing House, Incorported, 2014)
"This book intends to share insights and ideas about the basic dynamics of tourism. The book would discusses the very basic concepts, learn the philosophies related to tourism and enumerate the sectors as important elements of the industry."--Preface
First published in 2009.
First edition entered under Buen Santos.
Includes bibliographical references.
Keywords: Tourism; Tourism -- Philippines; Tourist trade